MODEL PEMBELAJARAN DRILL SUBTITUSI TERHADAP KEMAMPUAN MENULIS KALIMAT TUNGGAL PADA SISWA TUNARUNGU DI SEKOLAH LUAR BIASA - NADLIROH, (Jurnal Pendidikan Khusus, 2017)
ABSTRACT:The hearing disturbance which was experienced by the hearing impairment students would have impact to the obstruction of speech development especially in writing. It caused hearing impairment students get difficulty in arranging sentence. One of the learning models, which could help hearing impairment students toward writing simple sentence ability, was learning model of substitution drill in Indonesian lesson. This research purpose was to analyze the influence of drill learning model toward writing simple sentence ability to hearing impairment students. This research used pre experiment kind of research. The time applied in this research was 10 times meeting with 8 times intervention. The research design used was one group pre test post test design with 3 students as the subject. The research location was SLB Muhammadiyah Sidayu Gresik. The method of data collection was done by test and observation. The data analysis was statistic non parametric by using sign test. From the research result which was then analyzed using sign test formula, it was obtained Z counted (ZH) 1,73 while the value of Z table in 5% significant for one side test was Zt = 1,64. Based on the explanation above it could be concluded that the learning model of substitution drill influenced toward writing simple sentence ability to hearing impairment students of class V in SLB Muhammadiyah Sidayu Gresik.   Keywords: Learning model, substitution drill, writing sentence ability